Compreensão do processo de adoção e elaboração do relato integrado sob a perspectiva sensemaking de Karl Weick - Slewinski, Evelise (2016)
The accounting information modifies the meaning of a particular entity to the user. For this, the reporting entity performs the management of its information flow in an attempt to adapt to the changes in its information ecology and the needs of external users. In this sense, the initiative of Integrated Reporting emerges, with the fulcrum of holistic and cohesive information reporting, which shows how the organization creates value over time. Integrated Reporting emerges to fill an information gap, and its conceptual framework is based on principles that allow entities to recognize their individuality and still enable the dissemination of comparable information. Thus, Weick (1973) proposes that the existence of organizations derive from their processes, as these constitute it, remove the ambiguity of information and results in the creation of organizational significance towards ecological change, known as sensemaking. For this research, we start from the premise that the adoption, elaboration and disclosure of Integrated Reporting constitute an organizational process due to a discontinuity (the advent of the IIRC's initiative) and thus can extract its sensemaking. Therefore, from the theoretical perspective of Weick (1973, 1995) the aim of this exploratory qualitative research is to investigate how the sensemaking is attributed by the participants involved in the process of adoption and development of Integrated Reporting. A single case study of a company of the IIRC pilot program was conducted. The data collection techniques used were interviews, non-participant observation and documental research. Data were triangulated with Weick's model of organizing and properties of sensemaking (1973, 1995). It was concluded that the process of adoption and development of Integrated Reporting in the organization occurs by sharing meaning among participants involved. Thus, the reporting of integrated information results from the occurrence of the sensemaking imbricated in the structures and processes of information management of the organization. The results fill the gaps identified by Jensen and Berg (2012) and Stubbs and Higgins (2014) to contribute to the analysis of the reasons for the adoption of integrated reporting, internal mechanisms for the production of information and analysis on possible organizational changes resulting from adoption of integrated reporting.